If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(6x + 4) = 0 Reorder the terms: (-2 + x)(6x + 4) = 0 Reorder the terms: (-2 + x)(4 + 6x) = 0 Multiply (-2 + x) * (4 + 6x) (-2(4 + 6x) + x(4 + 6x)) = 0 ((4 * -2 + 6x * -2) + x(4 + 6x)) = 0 ((-8 + -12x) + x(4 + 6x)) = 0 (-8 + -12x + (4 * x + 6x * x)) = 0 (-8 + -12x + (4x + 6x2)) = 0 Combine like terms: -12x + 4x = -8x (-8 + -8x + 6x2) = 0 Solving -8 + -8x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + -4x + 3x2) = 0 Factor a trinomial. 2((-2 + -3x)(2 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -3x)' equal to zero and attempt to solve: Simplifying -2 + -3x = 0 Solving -2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 0 + 2 -3x = 0 + 2 Combine like terms: 0 + 2 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-0.6666666667, 2}
| 3(3+4x)=153 | | -5(6d-9.5)=-18.5 | | 5x+4=5x-8 | | 4p=2p+7 | | n-3/2=n-7/4 | | 8c-18=20 | | -4+4x=-1226x | | (100-x)/x=1.15 | | 13=17-5a | | 29-5q=22 | | 14=4n+5 | | 10m+8=21 | | 5(e+1)=3(2e-1) | | m^2+25m=0 | | 4(3x-2)+3(x+1)=100 | | 3p-4=10 | | 3x+2=42 | | x(x+2)=159+6(x+x+2) | | 8=3x^2-2x | | 8=3x*3x-2 | | X=3+0.25x | | X=3+0.25 | | 3Q=2P-M | | 2x-4u-5=0 | | (343)1/4(343)-1/12 | | 3(2p-7)=4p-5 | | f(-3)=-3 | | 8X+14=38+2x | | 8X+14=38+2 | | h^2-2h=0 | | 2x+3=10-3x | | 1/2X7 |